2016
DOI: 10.2174/1566524016666151222145551
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Restrains Pancreatic Duodenal Homeobox-1 (PDX-1) Function by Inhibiting ERK Signaling in Pancreatic Ductal Adenocarcinoma.

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is one of the most potent and perilous diseases known, with a median survival rate of 3-5 months due to the combination of only advanced stage diagnosis and ineffective therapeutic options. Metformin (1,1-Dimethylbiguanide hydrochloride), the leading drug used for type 2 diabetes mellitus, emerges as a potential therapy for PDAC and other human cancers. Metformin exerts its anticancer action via a variety of adenosine monophosphate (AMP)-activated protein kinase (AMPK)- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…Studies have shown that metformin facilitates the phosphorylation of AMPK indirectly through the action of the upstream kinase LKB1 [ 34 , 35 ]. In contrast to the known contribution of AMPK/LKB1 in metformin’s glucoregulatory activities, it remains unclear how metformins’ antiproliferative activity is regulated, and is still being debated [ 36 38 ]. A recent report indicated that metformin required AMPK, but not LKB1, to halt the proliferation of human non-small cell lung cancer cells [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that metformin facilitates the phosphorylation of AMPK indirectly through the action of the upstream kinase LKB1 [ 34 , 35 ]. In contrast to the known contribution of AMPK/LKB1 in metformin’s glucoregulatory activities, it remains unclear how metformins’ antiproliferative activity is regulated, and is still being debated [ 36 38 ]. A recent report indicated that metformin required AMPK, but not LKB1, to halt the proliferation of human non-small cell lung cancer cells [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our team demonstrated that metformin suppresses growth of PDAC cells via inhibition of PDX1 via a variety of adenosine monophosphate (AMP)-activated protein kinase (AMPK)-dependent and/or AMPKindependent mechanisms. We thus identified a potential novel mechanism by which metformin exerts its anticancer action through down-regulating PDX1 (25,26).…”
Section: Metformin Targets Pdx1 Via Inhibiting Erk Signalingmentioning
confidence: 99%
“…There are currently ten clinical trials in progress to determine whether metformin might prolong life for patients with pancreatic cancer 53, 54 . For these reasons, we chose to study and metformin and demonstrated that it suppresses growth of PDAC cells via inhibition of PDX1 via a variety of adenosine monophosphate (AMP)-activated protein kinase (AMPK)-dependent and/or AMPK-independent mechanisms 55 . (Figure 1).…”
Section: Small Molecules Targeting Pdx1-targeted In Pdacmentioning
confidence: 99%